Euthanasia in Colombia: Legal, Ecclesiastic and Cultural Aspects (Revista Iberoamericana de Bioética, 2019)
From two essential perspectives, the simplified and conclusive consolidation of legal, ecclesiastic and cultural formulations, and the conceptual appropriation that the patients, their families and their caretakers have, the topic of euthanasia in Colombia is addressed: legal, ecclesiastic and cultural aspects. With a qualitative methodology, we interview cancer patients and the staff that serve them with spiritual and material support, in order to assess the level of information that they handle, as well as the way such information determines their vital decisions regarding pain, suffering and death.
Keywords: euthanasia; policies; religion; culture; bioethics